Pakistan-China Relations: CPEC and Beyond. (1st January 2017) - ,
Abstract : This contribution is based on the proceedings of a session on the same title organized by the Institute of Policy Studies (IPS), Islamabad on August 10, 2017. The highlight of the event, as is recorded in this article, was the exclusive talk of H.E. Sun Weidong, Chinese ambassador to Pakistan while the opening and concluding remarks by Khalid Rahman, Executive President of IPS and Senator Raja Zafar-ul-Haq, Leader of the House in the Senate of Pakistan, respectively, are also part of the article. Pleasantries have been edited for the purpose of brevity and consistency.